Opiskelijoiden ja laajojen kielimallien vuorovaikutuksen kautta tapahtuva arvon yhteisluonti ja yhteistuhoaminen - Pasanen, Nelli (2025)
Artificial intelligence (AI) has transformed the way we operate and live. Also, the education sector has integrated artificial intelligence into its practices. The change in technology’s nature, from passive tool to an active participant em-phasized the importance of studying the interaction between human and AI. In recent years significant interest has been directed towards large language mod-els powered by generative AI. Previous studies have identified numerous ben-efits, but also drawbacks of student engagement with large language models. No previous studies have explored the interaction from the perspective of val-ue co-creation and co-destruction. Instead, research has primarily focused on human-robot interaction. Past research within the context of education has gen-erally studied the effects of AI and robotics. This study was conducted using a literature review and qualitative research methods. Participants were selected through a preliminary survey. Data collection was done through semi-structured interviews. The interviewees were individuals who had previously used ChatGPT in their studies. The data from the interviews were analyzed in relation to previous research. It allowed deeper understanding of the interac-tion between students and large language models, as well as the value that was either created or destroyed in the process. The value processes were primarily student-driven, influenced by prior experiences, general knowledge of the technology underlying these applications, and the student’s value drivers. However, the successful integration of resources alone does not guarantee a positive value process. This study supports previous research suggesting that positive and negative value processes occur simultaneously. Ultimately, the outcome is determined by an individual’s subjective perception of value.